Evolution of adolescents’ dietary patterns in Northeast Brazil from 2008 to 2018 - Machado, Soraia Pinheiro; Bezerra, Ilana Nogueira; Silva, Mariane Alves; D’oran, Maria Helena Lima; Cunha, Diana Barbosa; Moreno, Luis Alberto; Sichieri, Rosely (Revista de Saúde Pública, 2024)
OBJECTIVE: To evaluate the evolution of the dietary patterns of adolescents in the northeast region of Brazil. METHODS: Secondary analysis of data from the Pesquisa de Orçamentos Familiares (POF – Household Budget Surveys), collected by the Brazilian Institute of Geography and Statistics (IBGE) in the years 2008–2009 and 2017–2018. A total of 3,095 adolescents were evaluated in 2008–2009 and 3,015 in 2017–2018. Food consumption was assessed using two dietary records in 2008–2009 and two 24-hour recalls in 2017–2018, applied on non-consecutive days. Based on these data, principal components factor analysis (PCFA) was performed, followed by orthogonal rotation of the varimax type, to derive dietary patterns, stratified by sex. The results were described as means or percentage frequencies, with their respective 95% confidence intervals. RESULTS: Three main dietary patterns were identified among adolescents from the northeast region of Brazil. Among boys, in 2008–2009, the patterns were called snacks, traditional Brazilian, and coffee; and in 2017–2018, traditional Brazilian, snacks, and mixed, in this order of representativeness of the group’s eating habits. Among female adolescents, in 2008–2009, the patterns were snacks, traditional Brazilian, and coffee; and in 2017–2018, traditional Brazilian, snacks, and processed meats. CONCLUSION: The dietary patterns identified in 2008–2009 and 2017–2018 were similar in both genders; however, the snacks pattern, which explained most of the data variability in 2008–2009, was replaced by the traditional Brazilian.